Comparison of 3-D Printing and 5-axis Milling for the Production of Dental e-models from Intra-oral Scanning. Issue 1 (2nd January 2016) - Yau, H. T.; Yang, T. J.; Lin, Y. K.
ABSTRACT: Recently, chairside production in dentistry has garnered attention because of the time-saving, low-cost and high level of predictability of outcomes. Compared to traditional manufacturing using computer numerical control (CNC) milling machines, 3D printing plays a new and perhaps more important role in dental chairside production. The aim of this paper is to compare the dental e-models manufactured by 3D printer with those fabricated by CNC milling machines. In this paper, a patient with mal-positioned mandible was initially selected. Through an intra-oral scanner, the 3D STL model of the patient's denture was created. After that, a computer-aided virtual orthodontic treatment was planned. After planning, 8 steps were respectively fabricated by CNC milling machine and 3D printer. These models were digitized via a scanner and then compared with the original data from the virtual planning of orthodontic treatment. In the experiment, it is found that the smoothness and repeatability for CNC machining is better than for 3D printing, especially for inclined and curved surfaces such as occlusal surfaces. However, the 3D printer could produce concave and intricate geometry that is often not achievable by milling. GRAPHICAL ABSTRACT: